Streptococcal pneumonia meningitis as an initial presentation of X‐linked agammaglobulinemia: A case report and discussion. Issue 5 (17th September 2021) - Kadden, Daniel; Fowler, Grace; Engel, Elissa; Logan, Casey; Marathe, Kalyani; Gosdin, Craig
Abstract: X‐linked agammaglobulinemia (XLA) is a primary immunodeficiency caused by mutations in the gene for Bruton's tyrosine kinase (Btk), with affected males most commonly presenting with recurrent bacterial infections during the first few years of life. Here we present a 17‐month‐old male with a chief complaint of worsening rash and fever, whose history of streptococcal pneumonia meningitis at 5 months of age prompted suspicion for an underlying immunodeficiency and subsequent diagnosis of XLA. Bacterial meningitis is a rare initial presentation of XLA, and therefore physicians may easily overlook any underlying immunodeficiency. Prompt workup for immunodeficiency should be initiated in any vaccinated patient with a history of pneumococcal meningitis outside of the newborn period. Further discussion surrounding the various presentations of XLA, their related clinical manifestations and laboratory findings, and the importance of thorough chart review may encourage earlier diagnosis and initiation of treatment of this disease.